Respon Pertumbuhan Anggrek Dendrobium Terhadap Beberapa Jenis Pupuk Cair - Ni Komang Budiyani; I Wayan Sukasana; Putu Tirta Ariawan (Agriculture Faculty of Flores University, 2023)
This research is a study that uses plastic pots with a Randomized Block Design (RAK) for treatment which tested only one factor, namely the application of several types of liquid fertilizer, consisting of seven types and four replications so that 28 research pots were obtained. The results of the study aimed to determine the type of liquid fertilizer on the growth of Dendrobium Orchid can have a significant effect. The results prove that the type of fertilizer treatment on Dendrobium Orchid plants has a very significant effect (P < 0.01) on the parameters of root length, wet weight of plants on planting media, wet weight of plants under planting media, dry weight of plants above growing media, and total dry weight. It also had a significant effect (P < 0.05) on the parameters of the total wet weight and dry weight of plants under the Dendrobium Orchid growing media.